2009
DOI: 10.1002/mus.21555
|View full text |Cite
|
Sign up to set email alerts
|

Ocular myasthenia gravis in a senior population: Diagnosis, therapy, and prognosis

Abstract: The objectives of this study were (I) to explore the prognosis of ocular myasthenia gravis (OMG) in patients with onset at age 70 years and above (i.e. senior persons); (2) to identify predictors of secondary generalization in this age group; and 3) to address the effects of immunotherapy on this population of patients. We performed a retrospective analysis of 39 patients with myasthenia gravis who presented with only ocular signs and symptoms after age 70 years. Generalized myasthenia gravis (GMG) developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 34 publications
3
40
2
1
Order By: Relevance
“…Sommer et al 6 Previous studies have shown overall conversion rates of OMG to GMG of 50% to 64%. 2,4,12,13 Our series of OMG patients showed a much lower overall conversion rate of 20.9%, consistent with more recent retrospective studies reporting overall conversion rates ranging from 23% to 31%, 6,8,14,15 and this low conversion rate was observed in subjects with or without immunosuppressant therapy. Prior studies have emphasized the possible effect of immunotherapy on conversion rates.…”
Section: Discussionsupporting
confidence: 92%
“…Sommer et al 6 Previous studies have shown overall conversion rates of OMG to GMG of 50% to 64%. 2,4,12,13 Our series of OMG patients showed a much lower overall conversion rate of 20.9%, consistent with more recent retrospective studies reporting overall conversion rates ranging from 23% to 31%, 6,8,14,15 and this low conversion rate was observed in subjects with or without immunosuppressant therapy. Prior studies have emphasized the possible effect of immunotherapy on conversion rates.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the demographic data, the male predominance and the later age of disease onset in our patients with MG starting with ocular symptoms were striking observations. However, this particularity has been found previously, although in populations of patients with lower rates of subsequent generalization [12-14]. …”
Section: Discussionmentioning
confidence: 72%
“…To enable a better comparison of our findings with the previous results we compiled the generalization risks with or without early corticosteroid treatment observed in the previously published studies (Table 3). This crude comparison shows that, except for one small study [11], all other investigations find the generalization risks under corticosteroids to be below 17%, but without immunosuppressive treatment this risk increases to between 26% and 86%, corresponding to risk ratios of 0.14-0.32 [4,9,10,[12][13][14][15][16]]. An interesting question in this context is whether corticosteroids would reduce the risk of generalization only for the duration of the treatment or whether this possible protective effect could last on, even if the medication itself is discontinued or at least much reduced.…”
Section: Discussionmentioning
confidence: 94%
“…Six of the available seven small retrospective studies have identified a reduced generalization rate under steroids when assessed within the first 2 years of treatment with relative risks in the range from 0.14 to 0.32, whereas the seventh study observed an increased risk with corticosteroids [4,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%